The city as a text - Genovez, Patrícia Falco (2021)
Starting form some city concepts coming from some scholars (Mumford, Benveniste, Rapoport, Heidegger, Volli) this reflection aims understand urban phenomenology. The next step is the insight of the city as a text mainly from Lotman and Hjelmslev. The Itueta (Brazil) eradication and the West End (Boston - USA) reshuffle are examples of radical changings in the urban text and their effects over their inhabitants. The cultural, sociological and psychological changings – grief, psychological pathologies, discomfort – are at stake in this analysis. So, as conclusion: city is actually the end outcome of a text – as a write down and as a testimony – stablishing deep and meaningful relationships  to the life of its dwellers.